Studi Bahasa Sanskerta: Sebagai Metode Belajar Agama Hindu - Gede Agus Siswadi (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
Sanskrit is the language of Veda or the language used to describe the holy word of God, so it is very important for Hindus to know about the language of Sanskrit before studying Veda. In addition, all the concepts contained in Hinduism are derived from Sanskrit. Thus, Sanskrit is the earliest and basic language that Hindus must master in order to deepen Vedic teachings. The Sanskrit learning method really determines the success of learning, so the learning method needs to be adapted to the character and needs of learning.